Analisis Yuridis Tindak Pidana Pemerasan dan Pengancaman Melalui Media Elektronik (Studi Putusan Pengadilan Negeri Tanjung Jabung Timur Nomor: 83/PID.SUS/2022/PN.TJT) - Sihaloho, Hotman Natanael; Islah, Islah; Octaviany S, Nela (Universitas Batanghari Jambi, 2024)
This study aims to determine and analyse how the judge's consideration in the decision of the East Tanjung Jabung District Court Number: 83/Pid.Sus/2022/PN.Tjt and how the judge's decision in the decision of the East Tanjung Jabung District Court Number: 83/Pid.Sus/2022/PN.Tjt. The research method is normative juridical. The results of his research are that the legal considerations made by a judge are also one of the duties and obligations of a judge, namely the obligation to explore, follow, and understand the legal values and sense of justice that live in society. This becomes material that is processed to make legal considerations. It is also implied that a judge in carrying out his duties can carry out legal discovery or rechtvinding. And the Decision of the Judge of the East Tanjung Jabung District Court Number: 83/Pid.Sus/2022/PN.Tjt is the result of something that has been carefully considered and assessed beforehand by a judge in written or oral form. A judge's decision is a decision made by a judge after a criminal procedure procedure that contains a verdict of punishment or acquittal or release from all legal charges made in written form with the aim of resolving the case.